The Rubber Tappers' Monthly Wage Issue and the Impact of the Collective Agreement of 2003 - Parthiban Gopal (Kajian Malaysia, 2004)
The National Union of Plantation (NUPW), formed in 1954, is the sole representative of plantation workers in their negotiations for wages and better conditions of work with the employers body – the Malayan Agricultural Producers’ Association (MAPA). The mechanism used to determine the basic wage and other auxiliary payments to rubber tappers are linked to rubber price, land yield and labour productivity. Furthermore, other variables like agronomic practices and weather also affect earnings indirectly. In sum, this has resulted in earnings that fluctuate because of factors beyond the control of workers.